Multiphysics modeling of a reactivity insertion transient at different fidelity levels in support to the safety assessment of a SMART-like small modular reactor - Mercatali, Luigi; Huaccho, Gianfranco; Sanchez-Espinoza, Victor-Hugo (Frontiers in Energy Research, 2023)
Design basis accidents such as the control Rod Ejection Accident (REA) is evaluated as part of the deterministic safety analysis within the licensing processes for most of the current Small Modular Reactors (SMRs) designs. In this paper a study related to the neutronic and thermal-hydraulic coupled modelling of a REA transient for a boron-free SMART-like core at different fidelity levels is presented. Two different solutions for the core at hot zero power state (HZP) are provided; the first one is based on the standard nodal two-steps approach using the diffusion approximation and the second one is characterized by a more accurate high-fidelity scheme based on Monte Carlo neutron transport coupled to subchannel level thermal-hydraulics allowing performing full core pin-by-pin transient analysis. In the paper the details of the two different modelling approaches are presented and the corresponding results are compared one to each other, allowing on one side to verify the results of the high-fidelity modelling against a standard nodal-based solution and on the other side to highlight the added value when using a better resolution which allows to compute safety parameters at the local level with the consequent possibility to reduce the safety margins.